Novel rare missense variations and risk of autism spectrum disorder: whole-exome sequencing in two families with affected siblings and a two-stage follow-up study in a Japanese population. - Jun Egawa; Yuichiro Watanabe; Chenyao Wang; Emiko Inoue; Atsunori Sugimoto; Toshiro Sugiyama; Hirofumi Igeta; Ayako Nunokawa; Masako Shibuya; Itaru Kushima; Naoki Orime; Taketsugu Hayashi; et al. (PLoS ONE, 2015)
Rare inherited variations in multiplex families with autism spectrum disorder (ASD) are suggested to play a major role in the genetic etiology of ASD. To further investigate the role of rare inherited variations, we performed whole-exome sequencing (WES) in two families, each with three affected siblings. We also performed a two-stage follow-up case-control study in a Japanese population. WES of the six affected siblings identified six novel rare missense variations. Among these variations, CLN8 R24H was inherited in one family by three affected siblings from an affected father and thus co-segregated with ASD. In the first stage of the follow-up study, we genotyped the six novel rare missense variations identified by WES in 241 patients and 667 controls (the Niigata sample). Only CLN8 R24H had higher mutant allele frequencies in patients (1/482) compared with controls (1/1334). In the second stage, this variation was further genotyped, yet was not detected in a sample of 309 patients and 350 controls (the Nagoya sample). In the combined Niigata and Nagoya samples, there was no significant association (odds ratio = 1.8, 95% confidence interval = 0.1-29.6). These results suggest that CLN8 R24H plays a role in the genetic etiology of ASD, at least in a subset of ASD patients.